Design and development of battery pack for solar powered UAV - Chen, Jiahao (2015)
This report serves as a documentation of the author’s work on the Solar Unmanned Aerial Vehicle (UAV) project, during the author’s final year of study at Nanyang Technological University (NTU). This project is a collaboration between NTU and Defense Science Organisation (DSO) to develop a solar UAV, which is capable of at least 24 hours of continuous flight. The author worked as a member of solar energy team. This team was in charge of fabricating solar panels and battery packs, at the same time developing a control system between them. Firstly, the report details the designing and development of a battery pack for the solar powered UAV. Prototype is made to ensure the performance, functionality and specification. The Battery Management System (BMS) was introduced to control the charging and discharging of battery packs. It will monitor cell voltages and temperatures, and act on this information to protect the pack against being operated outside acceptable limits. The author will show the detail circuit diagrams including the battery pack and BMS. Lastly the author will study the properties of the solar cells. However, the solar cells are fragile and expensive, encapsulating of the solar cells is an important step before put them on the airfoil of a plane. A process of encapsulating of solar cells will be discussed in the chapter before conclusion.